Out of hospital cardiac arrest and uncontrolled donation after circulatory death in a tertiary cardiac arrest center. (August 2020) - Lazzeri, Chiara; Bonizzoli, Manuela; Franci, Andrea; Cianchi, Giovanni; Batacchi, Stefano; Ciapetti, Marco; Fulceri, Giorgio Enzo; Rugna, Mario; Peris, Adriano
Abstract : Objectives: Out of hospital cardiac arrest (OHCA) is worldwide quite a common disease, whose mortality still remains high. We aimed at assessing the number of potential donors after OHCA in a tertiary cardiac arrest center with extracorporeal membrane oxygenation (ECPR) and uncontrolled donation after circulatory death (uDCD) programs. Methods: In our single center, prospective, observational study (June 2016 to December 2018), we included all OHCA consecutive patients aged or less 65 years. Results: Our series included 134 OHCA patients. The percentage of patients with return of spontaneous circulation (ROSC) was 36% (48/134). Among patients with no ROSC, ECPR was implanted in 26 patients (26/86, 30%). Among patients without ROSC, 25 patients were eligible for uDCD (25/86, 29%), while 35 patients died at the emergency department. Among patients with ROSC, 15 patients died (15/48, 31%), among whom seven became donors after brain death (7/15, 49%), a percentage which did not vary during the study period. In the subgroup of the 26 patients treated with ECPR, 24 patients died (24/26, 92%) among whom eight were potential donors (33%, 8/34), and only two patients survived (7.7%, 2/26) though with good neurological outcome. Conclusions: The implementation of ECPR and uDCD programs in a tertiary cardiac center is feasible and increased the number of donors, because despite organizational and technical challenges, the uDCD donor pool was 62.5% of all potential donors (25/40).